2015
DOI: 10.1002/14651858.cd010259.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed dressing removal after primary closure of clean and clean-contaminated surgical wounds

Abstract: Early versus delayed dressing removal a er primary closure of clean and clean-contaminated surgical wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 34 publications
0
43
0
1
Order By: Relevance
“…Several studies addressing early versus delayed showering of patients with a surgical wound found no difference in the development of infections [127,128]. Furthermore, studies of early versus delayed dressing removal after primary closure summarised in a Cochrane database showed no apparently significant difference between early (up to 48 hours after surgery) and delayed (beyond 48 hours) removal [122]. Those findings were based on three small randomised controlled trials, so some uncertainty remains regarding the exact timing of dressing removal.…”
Section: Post-operative Prevention Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies addressing early versus delayed showering of patients with a surgical wound found no difference in the development of infections [127,128]. Furthermore, studies of early versus delayed dressing removal after primary closure summarised in a Cochrane database showed no apparently significant difference between early (up to 48 hours after surgery) and delayed (beyond 48 hours) removal [122]. Those findings were based on three small randomised controlled trials, so some uncertainty remains regarding the exact timing of dressing removal.…”
Section: Post-operative Prevention Measuresmentioning
confidence: 99%
“…Because the daily absorption of triclosan from these sutures is rather low, the chance of developing resistance remains low. Sutures impregnated with other antimicrobial agents are being tested [15], and wound dressings are used to provide physical support and protection from bacterial contamination and absorb exudate [121,122]. A Cochrane review analysed several studies that assessed the effect of wound dressings in preventing SSIs.…”
Section: Surgical Debridement and Irrigationmentioning
confidence: 99%
“…16 Dressings are thought to be a barrier that protects wounds from microorganisms in the outside environment. 72 Bathing and showering is also a controversial matter. 71 No evidence showed that a particular type of dressing was better than any other at preventing SSIs.…”
Section: Postoperative Phasementioning
confidence: 99%
“…In 2015, a Cochrane review concluded that early removal of dressings from surgical wounds appears to have no negative effect on the outcomes. However, this recommendation is based on very low quality evidence from three small trials . Dumville et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, this recommendation is based on very low quality evidence from three small trials. 14 Dumville et al con-cluded that there is not enough evidence to ascertain whether covering surgical wounds reduces the risk of infection. However, there is no absolute guidance regarding the timing of dressing removal.…”
mentioning
confidence: 99%